BETA Zeolite Thin Films Supported on Honeycomb Monoliths with Tunable Properties as Hydrocarbon Traps under Cold‐Start Conditions. Issue 8 (2nd July 2013) - Navlani‐García, Miriam; Varela‐Gandía, Francisco J.; Bueno‐López, Agustín; Cazorla‐Amorós, Diego; Puértolas, Begoña; López, José M.; García, Tomás; Lozano‐Castelló, Dolores
Abstract A high percentage of hydrocarbon (HC) emissions from gasoline vehicles occur during the cold‐start period. Among the alternatives proposed to reduce these HC emissions, the use of zeolites before the three‐way catalyst (TWC) is thought to be very effective. Zeolites are the preferred adsorbents for this application; however, to avoid high pressure drops, supported zeolites are needed. In this work, two coating methods (dip‐coating and in situ crystallization) are optimized to prepare BETA zeolite thin films supported on honeycomb monoliths with tunable properties. The important effect of the density of the thin film in the final performance as a HC trap is demonstrated. A highly effective HC trap is prepared showing 100 % toluene retention, accomplishing the desired performance as a HC trap, desorbing propene at temperatures close to 300 °C, and remaining stable after cycling. The use of this material before the TWC is very promising, and works towards achieving the sustainability and environmental protection goals.